Loss of mitochondrial transcription factor A in neural stem cells leads to immature brain development and triggers the activation of the integral stress response in vivo. - Rintaro Kuroda (Public Library of Science (PLoS), 2021)
Mitochondrial dysfunction is significantly associated with neurological deficits and age-related neurological diseases. While mitochondria are dynamically regulated and properly maintained during neurogenesis, the manner in which mitochondrial activities are controlled and contribute to these processes is not fully understood. Mitochondrial transcription factor A (TFAM) contributes to mitochondrial function by maintaining mitochondrial DNA (mtDNA). To clarify how mitochondrial dysfunction affects neurogenesis, we induced mitochondrial dysfunction specifically in murine neural stem cells (NSCs) by inactivating Tfam. Tfam inactivation in NSCs resulted in mitochondrial dysfunction by reducing respiratory chain activities and causing a severe deficit in neural differentiation and maturation both in vivo and in vitro. Brain tissue from Tfam-deficient mice exhibited neuronal cell death primarily at layer V and microglia were activated prior to cell death. Cultured Tfam-deficient NSCs showed a reduction in reactive oxygen species produced by the mitochondria. Tfam inactivation during neurogenesis resulted in the accumulation of ATF4 and activation of target gene expression. Therefore, we propose that the integrated stress response (ISR) induced by mitochondrial dysfunction in neurogenesis is activated to protect the progression of neurodegenerative diseases.